Developing an English for Specific Purposes (ESP) Module for the Staff of Syariah Faculty IAIN Pontianak - Syarifah Mawaddah (Universitas Sembilanbelas November Kolaka, 2021)
This present study aims to develop practical materials for the staff in Sharia faculty IAIN Pontianak to improve their professional and communication skills. The material was produced in the form of module that focused on speaking skills in context and was designed in a way that can addrees the learning need of the staff in Sharia faculty IAIN Pontianak. This study addapts ADDI model in developing the material; analyze, design, develop and implement. In collecting the data for this research, the writer interviews the staff. The results of the interview become the foundation for the writer to develop the material. The finding of this study is in the form of module that covers the daily English expressions that are used in work place. The material from this study can help the staff to express themselves in English in relation to their work. Since the evaluation phase from the ADDI model was not conducted, it is recommended for the future research to evaluate the product that has been developed in this study. Keywords: ESP, module, staff.